2005
DOI: 10.1073/pnas.0407523102
|View full text |Cite
|
Sign up to set email alerts
|

The RNA-binding protein HuD regulates neuronal cell identity and maturation

Abstract: Neural Hu proteins (HuB͞C͞D) are RNA-binding proteins that have been shown to induce neuronal differentiation activity when overexpressed in immature neural progenitor cells or undifferentiated neuronal tumors. Newly generated HuD-deficient mice exhibited a transient impaired-cranial-nerve-development phenotype at an early embryonic stage. Adult HuD-deficient mice exhibited an abnormal hind-limb reflex and poor rotarod performance. Analysis of neurosphere formation revealed that the number and self-renewal cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
189
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(198 citation statements)
references
References 30 publications
7
189
2
Order By: Relevance
“…A considerable body of literature demonstrates the importance of nElavls in neuronal differentiation and the PTR of mRNAs involved in neuronal excitation and synaptic plasticity. [7][8][9][10] On the contrary, HuR was considered as a redundant factor in neurons; recent evidence contradicts this supposition. Genetic ablation and molecular experiments demonstrated that HuR can promote the renewal of neuronal progenitors, whereas in differentiated cells it is silenced by nElavls via the alternative polyadenylation of its mRNA.…”
mentioning
confidence: 79%
“…A considerable body of literature demonstrates the importance of nElavls in neuronal differentiation and the PTR of mRNAs involved in neuronal excitation and synaptic plasticity. [7][8][9][10] On the contrary, HuR was considered as a redundant factor in neurons; recent evidence contradicts this supposition. Genetic ablation and molecular experiments demonstrated that HuR can promote the renewal of neuronal progenitors, whereas in differentiated cells it is silenced by nElavls via the alternative polyadenylation of its mRNA.…”
mentioning
confidence: 79%
“…Overexpression of HuC or HuD in PC12 cells increased the rate of neuronal differentiation, whereas down-regulation resulted in an impairment of neurite growth (55,56). Likewise, a decrease in neuronal differentiation was observed in HuD null mutant mice (57). Although HuC/D proteins are strong candidates to modulate the neuronspecific activity of Prrxl1 5Ј-UTR-A, their involvement remains to be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…Given the number and variety of transcripts with AREs, HuD is implicated in multiple neuronal and cellular functions (for review, see Deschênes-Furry et al, 2006). For instance, cell-culture studies, and more recently studies performed with HuD knock-out mice, have demonstrated that HuD has a significant role in promoting cellcycle exit (Marusich et al, 1994;Okano and Darnell, 1997;Akamatsu et al, 2005), differentiation, and neurite elongation (Aranda-Abreu et al, 1999;Mobarak et al, 2000;Anderson et al, 2001). Within the adult CNS, HuD has also been implicated in the plasticity of hippocampal neurons during various learning paradigms (Quattrone et al, 2001;Bolognani et al, 2004;Pascale et al, 2004).…”
Section: Discussionmentioning
confidence: 99%